Investigation of the Relationship Between Psychopathological Symptoms, Acculturation, and University Adjustment Among Students from Eastern and Western Türkiye Studying in the TRNC - Merve Nehir Kurt; Mehmet Çakıcı; Atakan Taşkıran (Clinical Journal of Health Sciences, 2026)
The aim of this study was to compare the acculturation attitudes, university adjustment levels, and psychopathological symptoms of university students from the eastern and western regions of Türkiye studying in the Turkish Republic of Northern Cyprus (TRNC), and to examine the relationships among these variables. This descriptive cross-sectional study included a total of 100 university students enrolled at Near East University, comprising 50 students from the eastern regions and 50 students from the western regions of Türkiye. Data were collected using the Sociodemographic Information Form, the Symptom Checklist-90-Revised (SCL-90-R), the Acculturation Scale, and the University Life Scale. Descriptive statistics, independent-samples t tests, and Pearson correlation analysis were used to analyze the data. After Bonferroni correction for multiple comparisons, only the differences in the integration, separation, and marginalization subscales of the Acculturation Scale remained significant (p < .001), with students from the western region scoring higher on these subscales. The higher somatization, psychoticism, and additional-scale scores among eastern-region students, and the higher assimilation and personal adjustment scores among western-region students, did not survive the correction and were therefore interpreted as exploratory findings. Correlation analyses revealed no significant relationship between acculturation attitudes and university adjustment among students from the eastern region. However, among students from the western region, higher assimilation scores were associated with lower university environment adjustment and emotional adjustment, whereas higher separation scores were associated with lower university environment adjustment and social adjustment (p < .05). The findings indicate that acculturation attitudes, psychopathological symptoms, and university adjustment differed according to students' region of origin, and that these variables were associated with one another. In particular, acculturation attitudes were associated with specific dimensions of university adjustment among students from the western region. These findings may contribute to the development of psychosocial support services and adjustment programs for university students with diverse sociocultural backgrounds.